Perluasan Pemasaran dan Penjualan Produk Paguyuban Warsamundung Melalui Digital Marketing dan Pengembangan Website Komunitas - Mujib, Miftachul; Ratnawati, Shinta; Ikhwan, Khairul; Musthafa, Afif; Syakina, Nadia; Setianingsih, Yunita (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2025)
The Warsamundung Disability Association in Magelang Regency has many economically independent members who produce various handicrafts and processed foods. Despite their potential for economic growth, they face several operational challenges. The main challenges include a lack of knowledge about digital marketing, weak managerial skills, and limited access to a wider market. To address these challenges, a community service program was designed to enhance members' capacity by improving their understanding of digital marketing and developing marketing channels for their products. This program aims to improve human resource capacity, expand market access, increase sales turnover, and create more sustainable businesses. The community service method involves surveying partner needs, formulating programs, implementing programs with digital marketing techniques, and developing websites as a promotional and marketing medium. The expected outcome of this community service program is that members of the Warsamundung Disability Association can optimize their economic potential by expanding marketing and increasing product sales.